Barodontalgia: Dental Implications at High Altitudes - Nikita Sahu1, Debasruti Naik2, Sudipta Sahu1, Kajal Kiran Sahu3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Barodontalgia is a symptom of a pre-existing subclinical oral diseases rather than a pathological conditionitself. It was considered earlier as a “flyer’s toothache,” barodontalgia is described as pain that occurs in thetooth utilizing changes in ambient pressure usually in people who fly or dive. It is the whole responsibilityof the dental health professionals to provide the aviators with the best dental treatment as well as awarenessabout the hazards to the dental treatments at higher altitudes. This piece of writing gives sufficient informationabout the need and protocols to be followed especially for the patients commonly at higher altitudes. Thisarticle aims at providing adequate knowledge about barodontalgia and the responsibilities towards itsprevention both by the dentist and the flight crew members.